ISOLATION AND CHARACTERIZATION OF MESORHIZOBIUM STRAINS FROM WILD AND CULTIVATED CHICKPEA NODULES IN THE KURDISTAN-IRAQ - Abdulla, Ashti Sleman; Ahmad , Nariman S.; Bahramnejad, Bahman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The study was conducted to investigate symbiosis and node-forming ability of Mesorhizobium bacteria in chickpea (Cicer arietinum L.) growth under challenging environmental conditions. Nodules were collected from wild and cultivated chickpeas in the Kurdistan Region. Endophytic bacteria associated with their roots were isolated and characterized. All the 30 isolates, were found to be gram-negative with smooth, circular colonies. Most isolates (80%) were mucoid, while 20% were not and produced green colonies on bromothymol blue. Half of the isolates 50%) grew best in alkaline pH (6.6-10.5), 26.6% thrived in acidic pH (3.5-5.5), and 20% preferred neutral pH. Regarding salt tolerance, 63% of the isolates grew well in 0-4% NaCl, while 6.67% tolerated up to 6% NaCl. In terms of temperature, 56.67% grew better in the range of 15-35°C, while 36.67% thrived in 25-40°C. Some isolates had slow growth in alkaline conditions, producing blue colonies, while fast-growing isolates in acidic conditions yielded yellow colonies. This research provides insights into the adaptability of these bacteria under harsh conditions of high pH, salinity, and extreme temperatures. The outcomes offering a pathway to improving chickpea resilience and productivity in marginal lands of the Kurdistan Region and similar sites worldwide, through utilizing indigenous candidate rhizobia for adverse environments.